Opened Ground : Selected Poems, 1966-1996 - Seamus Heaney (New York, United States Farrar, Straus & Giroux Inc, 1999)
As selected by the author, Opened Ground includes the essential work from Heaney's twelve previous books of poetry, as well as new sequences drawn from two of his landmark translations, The Cure at Troy and Sweeney Astray, and several previously uncollected poems. Heaney's voice is like no other--by turns mythological and journalistic, rural and sophisticated, reminiscent and impatient, stern and yielding, curt and expansive (Helen Vendler, The New Yorker)--and this is a one-volume testament to the musicality and precision of that voice. The book closes with Heaney's Nobel Lecture: Crediting Poetry.
Keywords: Poetry -- Poetry